Wide Awake Local Anesthesia No Torniquet in Hand Surgery - Sharma, Aditi; Khurram, Md. Fahad (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
This paper presents a study on wide awake local anesthesia no torniquet in hand surgery.
Keywords: WALANT; Hand surgery